Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

Interfacial microdomain engineering using Zn-halloysite nanotubes for advanced electrochemical sensing of nitrite in food matrices - Arunkumar Selvam; Esakkimuthu Shanmugasundaram; Sathish Marimuthu; Balakrishnan Thangavelu; Chih-Yu Kuo; Mani Govindasamy; Mohamed A. Habila (Analytica Chimica Acta, 2026)

Water safety evaluation through sensitive thymol quantification using NiCo MOF@f-CB nanocomposite - Arunkumar Selvam; Gopika Meenakumari Gopakumar; Beena Saraswathyamma; Mohamed A. Habila; Chih-Yu Kuo; Mani Govindasamy (Journal of Water Process Engineering, 2026)

A synergistic approach to water purification: SERS-assisted detection and nanofiltration of contaminants in natural rubber wastewater using graphene oxide noble-metal nanocomposites - I.Anushma Jeffrin; Arunkumar Selvam; R. Parimaladevi; Vasant Sathe; Mohamed A. Habila; Chih-Yu Kuo; M. Umadevi (Journal of Environmental Chemical Engineering, 2026)

A reliable design on real-time electrochemical detection of 5-nitro-2-furaldehyde in various foods and biofluids using NiCo2O4@ g-C3N4 matrix - B. Sudharsan Bangaru; Arunkumar Selvam; Asma A. Alothman; S.K. Suresh Babu; Chih-Yu Kuo; Mani Govindasamy (Chemical Engineering Journal, 2026)

Computational screening of lichen bioactive compounds as a potential antiviral agent against SARS-CoV-2 main proteases - S. Jeya Preethi; A. Yamuna; M. Arunkumar; E. Murugesh; P. Ponmurugan; P. Shanmughavel (In Silico Pharmacology, 2026)

Electrochemical monitoring of vanillin using BaFe12O18@carbon black modified electrode in food samples - Keerthana Periyasamy; Gopika Meenakumari Gopakumar; Arunkumar Selvam; Beena Saraswathyamma; Norah A. Albassami; Mohd Taukeer Khan; Chih-Yu Kuo; Mani Govindasamy (Food Chemistry, 2026)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Response of foxtail orchid (Rhynchostylis retusa L. Blume.) restoration on various hosts in East Siang district, Arunachal Pradesh - Ruchika Borbaruah; Preeti Hatibarua; Arunkumar Phurailatpam; Sunil Kumar; N. Surmina Devi; Prashant Kisan Nimbolkar; A. S. Mailappa (Plant Ecology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effect of age-associated oxidative stress on sperm viability, acrosomal integrity and sperm apoptosis and DNA fragmentation in Sahiwal breeding bulls - Vinod Kumar Gupta; Tushar Kumar Mohanty; Mukesh Bhakat; A. Kumaresan; Rubina K. Baithalu; Nishant Kumar; Raju Kumar Dewry; Dipti Nain; Rishipal Yadav; Ramasamy Arunkumar; Aye Soe (Veterinary Research Communications, 2025)

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Contrasting gut bacteriomes unveiled between wild Antheraea assamensis Helfer (Lepidoptera: Saturniidae) and domesticated Bombyx mori L. (Lepidoptera: Bombycidae) silkworms - Gangavarapu Subrahmanyam; Yeruva Thirupathaiah; N. Vijay; Rajal Debnath; K. P. Arunkumar; Mallikarjuna Gadwala; Prashant A. Sangannavar; S. Manthira Moorthy; Mahananda Chutia (Molecular Biology Reports, 2024)

Efficiency of female age of egg parasitoids on parasitism of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) eggs of various ages - K. Veena; Arunkumar Hosamani; A. Prabhuraj; Shivanand G. Hanchinal; Mallikarjun Kenganal; Sharanabasappa S. Deshmukh (Journal of Plant Diseases and Protection, 2024)

Impact of air pollutants on climate change and prediction of air quality index using machine learning models - Gokulan Ravindiran; Sivarethinamohan Rajamanickam; Karthick Kanagarathinam; Gasim Hayder; Gorti Janardhan; Priya Arunkumar; Sivakumar Arunachalam; Abeer A. AlObaid; Ismail Warad; Senthil Kumar Muniasamy (Environmental Research, 2023)

Synthesis and characterization of calcium oxide nano particles obtained from biowaste and its combustion characteristics in a biodiesel operated compression ignition engine - J. Jayaprabakar; A. Karthikeyan; K. Vijai Anand; T. Arunkumar; N. Anbazhaghan; Gayathri Rangasamy (Fuel, 2023)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

Efficacy of Eisenia bicyclis phlorotannins in the treatment of diabetes and reducing inflammation - Rathinam Raja; Shanmugam Hemaiswarya; Kulanthaiyesu Arunkumar; N. Mathiyazhagan; Sabariswaran Kandasamy; A. Arun; P. Ramasamy (Food Bioscience, 2023)

Direct, indirect, post-infection damages induced by coronavirus in the human body: an overview - Sivan Padma Priya; P. M. Sunil; Sudhir Varma; Carel Brigi; Mohammad Faruq Abd Rachman Isnadi; J. A. Jayalal; R. Arunkumar Shadamarshan; S. Suresh Kumar; Neela Vasantha Kumari; Rishi P. R. Kumar (VirusDisease, 2022)

Indian rosewood (Dalbergia latifolia Roxb.): biology, utilisation, and conservation practices - A. N. Arunkumar; Rekha Ravindranath Warrier; Mafatlal M. Kher; Jaime A. Teixeira da Silva (Trees, 2022)

Genetic Diversity and Population Structure in Fragmented Natural Populations of Melia dubia Cav. Revealed by SSR Markers—Its Implications on Conservation - Swati Rawat; Annapurna D.; Arunkumar A. N.; Geeta Joshi (Plant Molecular Biology Reporter, 2022)

Phosphorus dynamics and solubilizing microorganisms in acid soils under different land uses of Lesser Himalayas of India - Ranjan Paul; Raj Deo Singh; A. K. Patra; D. R. Biswas; Ranjan Bhattacharyya; K. Arunkumar (Agroforestry Systems, 2017)

Characterization of mode of reproduction in Commiphora wightii [(Arnot) Bhandari] reveals novel pollen–pistil interaction and occurrence of obligate sexual female plants - K. A. Geetha; Aarti Kawane; Ashok Kumar Bishoyi; Arunkumar Phurailatpam; C. Ankita; S. K. Malik; R. Srinivasan; S. R. Bhat (Trees, 2013)

Identification of sex-specific DNA markers in betel vine (Piper betle L.) - Sanghamitra Samantaray; Arunkumar Phurailatpam; Ashok Kumar Bishoyi; K. A. Geetha; Satyabrata Maiti (Genetic Resources and Crop Evolution, 2012)

Quercetin downregulates matrix metalloproteinases 2 and 9 proteins expression in prostate cancer cells (PC-3) - M. R. Vijayababu; A. Arunkumar; P. Kanagaraj; P. Venkataraman; G. Krishnamoorthy; J. Arunakaran (Molecular and Cellular Biochemistry, 2006)